Linguistic features of argotic lexicon in private correspondence in penal institutions (Eurasian Journal of Philology Science and Education, 2016)
The purpose of this article is the description of studying of the functional and stylistic characteristic of argotizm in private notes of convicts. Taking into account specifics of object of studying the included supervision was applied; the analysis of language material was carried out by means of descriptive, comparative and comparative and statistical methods, methods of generalization. Actively the origin, formation and functioning of a slang, his interaction with other language systems and transition toother forms of national language began to be investigated. The functional and stylistic description of argotic lexicon in private correspondence can be understood as classification of lexemes by these or those bases. It is possible to classify argotic lexicon taking into account the instruction on importance of those aspects of culture which names make synonyms in language.
Keywords: slang; paradigm; classification; argotic lexicon